1. First, distribute the 5 on the left side of the equation to simplify it:
5(2x - 8) = 10x - 40
Therefore, the equation becomes:
10x - 40 + 15 = -15
2. Next, combine like terms on the left side of the equation:
10x - 40 + 15 = 10x - 25
Therefore, the equation becomes:
10x - 25 = -15
3. Add 25 to both sides of the equation to isolate the variable term:
10x - 25 + 25 = -15 + 25
10x = 10
4. Divide both sides of the equation by 10 to solve for x:
10x/10 = 10/10
x = 1
5. Therefore, the solution to the equation is x = 1.
An equation is shown below:
5(2x - 8) + 15 = -15
Write the steps you will use to solve the equation and explain each step.
1 answer